Correlations between the components of physical readiness and physical development of the older preschoolers - N. A. Kulyk; I. P. Maslyak (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The indices of interdependence of physical fitness and physical development of children by means of correlation and factor analysis. The study involved 276 children aged 5-6 years. Found that in early childhood education important place occupied by the study of the physical condition of children. Reflected the degree of the relationship between the results of measurements of body length, body weight, volume of the chest, heart rate, blood pressure, lung capacity, breath-holding time (Stange's Genchi test) and measures of the level of development of basic physical properties ( strength, speed, flexibility, endurance and coordination abilities ). Research indicates the presence of interaction between the indices motor fitness and physical development of preschool children. The most significant effect on the physical health of the ability to provide coordination, speed and power capacity, speed and endurance.